Fertilization, hatching, and survival rates in the hybrid Catfish Clarias gariepinus x Clarias macrocephalus produced through triploid induction using cold shock treatment. - Monteclaro, Jan Eilene
Freshwater fishes are important sources of relatively cheap animal protein for the people in the developing countries in Asia, and fisheries and aquaculture of these food fishes must be sustained., The Clariids, a family of catfish to which the African catfish (Clarias gariepinus) and the native catfish (C. macrocephalus) belong have a wide geographical distribution and are found in North Central and South America, Africa, Eurasia, Southeat Asia, Japan, and Australia. Induced triploidization has been introduced in different hybrids of catfish in order to produce a sterile fish and at the same time to increase production. Such genetically sterile catfish can be produced by artificial retention of the second polar body by using thermal shocking technique, specifically cold shock. This paper was conducted to induce triploidy in the hybrid cross between Clarias gariepinus (male) and C. macrocephalus (female) and to specifically compare fertilization, hatching and survival rates between treatments. Induction of triploidy was carried out by exposing the artificially fertilized eggs at 5 degrees, 7 degrees, and 9 degrees centigrade thermal shocks for 15 minutes. Based on the experimental results, between treatments, hybrids exposed at 9 degrees centigrade have better performance as determined by its high fertilization (90.667 percent), hatching (90.435 percent) and survival (91.866 percent) rates. Therefore, it is recommended that this temperature setting be the one used in thermal shocking to produce optimal results.